New organic substrates and boron fertilizing for production of yellow passion fruit seedlings - Salustriano da Silva-Matos, Raissa Rachel; Silva, Gabriel Barbosa da [UNESP]; Marques, Adenaelson de Souza; Monteiro, Maciel Lima; Lucena Cavalcante, Italo Herbert; Osajima, Josy Anteveli (Taylor & Francis Ltd, 2016)
The identification of alternative substrates suitable for seedling production is very important, while boron nutrition is also relevant due to plant requirement and its difficult management. Thus, four experiments were carried out from October 2012 to April 2013 to evaluate the effect of substrates using decomposed buriti (Mauritia vinifera Mart.) stem (DBS) and boron fertilizing for seedling production of yellow passion fruit (Passiflora edulis Sims). The experimental design was completely randomized in factorial scheme 6x2+1, referring to the substrates [S1: DBS, S2: soil and sand 1:1 (20%) + DBS (80%), S3: soil and sand 1:1 (40%) + DBS (60%), S4: soil and sand 1:1 (60%) + DBS (40%), S5: soil and sand 1:1 (80%) + DBS (20%), S6: commercial substrate (additional treatment) and S7: soil, sand and manure 1:1:2] with and without boron. The seedling emergence, emergence rate, plant height, stem diameter, root length, root volume and dry mass of roots and shoots were recorded. The substrates S2 (without B fertilizing) and S4 (B fertilized with 0.5mg dm(-3)) produced seedlings with more than 3.0g of shoot dry mass and at least 30cm in height, and can be used for production of high-quality yellow passion fruit seedlings.
Keywords: Passiflora edulis Sims; seedling quality; growing media; boron